2005
DOI: 10.1111/j.1529-8817.2005.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution mtDNA Studies of the Indian Population: Implications for Palaeolithic Settlement of the Indian Subcontinent

Abstract: SummaryThe population of the Indian subcontinent represents a very complex social and cultural structure. Occupying a geographically central position for the early modern human migrations, indications are that the founder group that migrated out of East Africa also reached India. In the present study we used the twin strategy of mapping the whole mitochondrial DNA (mtDNA) using the standard 14 restriction enzymes, and sequencing the non-transcribed HVSI region, to derive maximum maternal lineages from a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Three of them had the 16359 transition that was diagnostic of the M1a East African cluster, and the remaining one belonged to the rare but widespread M1b1 cluster characterized in the HVSI region by 16185 transition and the 16190d deletion that had been identified in the northwest Africa, Jordan, and the Iberian Peninsula [27]. The other three M sequences belonged to Indian clades.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of them had the 16359 transition that was diagnostic of the M1a East African cluster, and the remaining one belonged to the rare but widespread M1b1 cluster characterized in the HVSI region by 16185 transition and the 16190d deletion that had been identified in the northwest Africa, Jordan, and the Iberian Peninsula [27]. The other three M sequences belonged to Indian clades.…”
Section: Resultsmentioning
confidence: 99%
“…Ethiopia was again the most likely source. However, the sole M1b1 Saudi sequence probably reached the Arabian Peninsula from northwest Africa through the Levantine corridor because this sequence has been reported repeatedly in west Africa, the Iberian Peninsula, and Jordan [27], but not yet in Ethiopia. Based on Y-chromosome studies, this northern route was proposed as an important path for bidirectional human migration between north Africa and the Levant [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Besides harboring such an important geographical position in Indian subcontinent, the origin and migration of several populations living in various regions in this state of India and their affinity with other contemporary South Asian population has not been explored, so far, at the high resolution level. The available genetic source of this region is poorly known due to less sample sizes and low resolution [19], [20]. Moreover, this state works as a bridge among central, northern and southern parts of India and might give some clues for the peopling of Indian subcontinent, placing it on the way of coastal route migration [3], [5].…”
Section: Introductionmentioning
confidence: 99%
“…These groups, supposedly the earliest inhabitants, embrace potential clues to the peopling of India in the past (Thapar, 1966;Cavalli-Sforza et al, 1994). They are also expected to provide further insights into past genetic history of human evolution as the molecular genetic studies have shown that the Indian subcontinent served as a major corridor and a transit stage for migration and expansion of Man out of Africa to other regions of the globe especially to Southeast Asia and Oceania (Cann et al, 1987;Excoffier and Langaney, 1989;Ingman et al, 2000;Templeton, 2002;Basu et al, 2003;Kivisild et al, 2003;Barnabas et al, 2006;Chaubey et al, 2007). In view of their importance, an investigation of the genetic affinity and diversity of these culturally and linguistically diverse regional tribes of the subcontinent is crucial.…”
mentioning
confidence: 99%